Preliminary assays on electrochemically modulated liquid-liquid extraction of metformin - Jajuli, M.N. (Penerbit Universiti Sains Malaysia, 2019)
Liquid-liquid extraction is one of the analytical methods that is commonly used for separation of various analytes. Nevertheless, the method is not capable to operate with hydrophobic medical drugs, particularly metformin where the drug is essentially used as an antidiabetic (Type II diabetes). Preliminary studies on extractions of metformin, phenyl biguanide and propranolol were accomplished using electrochemically modulated liquid-liquid extraction (EMLLE) method as a sample preparation method. The principle is based on application of electrically driving force to transfer the desired ions across the interface between two immiscible electrolyte solutions (ITIES). The extraction of three cationic drugs from artificial urine to 1, 2-dichoroethane, is controlled by external polarisation. By using ITIES cells, all of the drugs are found to transfer within the available potential window. The application of different galvani potential differences enables the selective extraction of drugs. Potential window of artificial urine shorter than lithium chloride as aqueous phase. Nevertheless, for both cases, the first drug to be extracted is propranolol which is the most hydrophobic drug and hence a lower potential is needed to transfer this cationic molecule across the interface as followed by phenylbiguanide and metformin. Â© Penerbit Universiti Sains Malaysia, 2019.